RC2S: A Cognitive Remediation Program to Improve Social Cognition in Schizophrenia and Related Disorders - Peyroux, Elodie; Franck, Nicolas (Frontiers in Human Neuroscience, 2014)
In people with psychiatric disorders, particularly those suffering from schizophrenia and related illnesses, pronounced difficulties in social interactions are a key manifestation. These difficulties can be partly explained by impairments in social cognition, defined as the ability to understand oneself and others in the social world, which includes abilities such as emotion recognition, theory of mind (ToM), attributional style, and social perception and knowledge. The impact of several kinds of interventions on social cognition has been studied recently. The best outcomes in the area of social cognition in schizophrenia are those obtained by way of cognitive remediation programs. New strategies and programs in this line are currently being developed, such as RC2S (cognitive remediation of social cognition) in Lyon, France. Considering that the social cognitive deficits experienced by patients with schizophrenia are very diverse, and that the main objective of social cognitive remediation programs is to improve patients’ functioning in their daily social life, RC2S was developed as an individualized and flexible program that allows patients to practice social interaction in a realistic environment through the use of virtual reality techniques. In the RC2S program, the patient’s goal is to assist a character named Tom in various social situations. The underlying idea for the patient is to acquire cognitive strategies for analyzing social context and emotional information in order to understand other characters’ mental states and to help Tom manage his social interactions. In this paper, we begin by presenting some data regarding the social cognitive impairments found in schizophrenia and related disorders, and we describe how these deficits are targeted by social cognitive remediation. Then we present the RC2S program and discuss the advantages of computer-based simulation to improve social cognition and social functioning in people with psychiatric disorders.